Static and Dynamic Stretching Differences Toward Knee Joint Extension in The Elderly - Nian Afrian Nuari; Andika Siswoaribowo; Efa Nur Aini (Journal of Ners and Midwifery, 2022)
The problem of a decrease in knee joint extension makes it difficult for the elderly to carry out their daily activities. Static and dynamic stretching exercises can help to maintain joint range of motion and minimize muscle flexibility loss. The goal of this research was to identify if static and dynamic stretching had different effects on knee joint extension in the elderly. With a pre-experimental research design, this research used a two-group pre-test post-test design. The participants in this research were divided into two groups: static stretching and dynamic stretching, with each group consisting of 18 people recruited by the purposive selection technique. Before and after the intervention, a goniometer was utilized to evaluate knee joint extension. To investigate the difference in influence, the Independent T-Test statistical evaluation was utilized, demonstrating that static and dynamic stretching had different effects on knee joint extension in the elderly. Both of these treatments had the ability to influence joint extension. Static stretching relaxes the muscles, allowing them to stretch further by moving one leg alternately and retaining the maximal position. Dynamic stretching increases joint flexibility by moving both legs simultaneously and slowly. This static and dynamic stretching is necessary for the elderly to avoid a reduction in joint extension during daily activities.